A review of the efficacy of neuromuscular electrical stimulation in critically ill patients. (January 2014) - Williams, Nicola; Flynn, Maria
Abstract Background: Muscle wasting in critical illness has been identified as a major clinical concern which can lead to persistent muscle weakness, impede recovery and limit physical function and quality of life in survivors. Neuromuscular electrical stimulation (NMES) has been suggested as an alternative to active exercise in critically ill patients. Objectives: To evaluate the efficacy of NMES in critically ill patients by evaluating the research literature. Methods: Structured database searches of the Cochrane Library, Ovid (Medline), CINHAL, Scopus and PEDro were completed. Results: Eight papers were retrieved and methodological quality evaluated using the Critical Appraisal and Skills Program tool. The NMES protocols, outcomes and findings were analysed and, given the methodological heterogeneity, the study findings were synthesised as a narrative. Analysis showed minimal adverse effects in the use of NMES and some potential benefits of NMES on preservation of muscle strength, decreased duration of mechanical ventilation and shorter Intensive Care Unit (ICU) length of stay. Conclusions: Evidence of the clinical benefits of NMES in the ICU is inconclusive and provides minimal guidance for use in clinical practice. There is a need for further research in this area.